Sterol Carrier Protein-2, a Nonspecific Lipid-Transfer Protein, in Intracellular Cholesterol Trafficking in Testicular Leydig Cells - Li, Nancy C. (PLoS One, 2016)
Sterol carrier protein-2 (SCP2), also called nonspecific lipid-transfer protein, is thought to play a major role in intracellular lipid transport and metabolism, and it has been associated with diseases involving abnormalities in lipid trafficking, such as Zellweger syndrome. The Scp2 gene encodes the 58 kDa sterol carrier protein-x (SCPX) and 15 kDa pro-SCP2 proteins, both of which contain a 13 kDa SCP2 domain in their C-termini. We found that 22-NBD-cholesterol, a fluorescent analog of cholesterol and a preferred SCP2 ligands, was not localized in the peroxisomes. This raises questions about previous reports on the localization of the SCPX and SCP2 proteins and their relationship to peroxisomes and mitochondria in intracellular cholesterol transport. Immunofluorescent staining of cryosections of mouse testis and of MA-10 mouse tumor Leydig cells showed that SCPX and SCP2 are present in both mouse testicular interstitial tissue and in MA-10 cells. Fluorescent fusion proteins of SCPX and SCP2, as well as confocal live-cell imaging, were used to investigate the subcellular targeting of these proteins and the function of the putative mitochondrial targeting sequence. The results showed that SCPX and SCP2 are targeted to the peroxisomes by the C-terminal PTS1 domain, but the putative N-terminal mitochondrial targeting sequence alone is not potent enough to localize SCPX and SCP2 to the mitochondria. Homology modeling and molecular docking studies indicated that the SCP2 domain binds cholesterol, but lacks specificity of the binding and/or transport. These findings further our understanding of the role of SCPX and SCP2 in intracellular cholesterol transport, and present a new point of view on the role of these proteins in cholesterol trafficking.